Clinical and functional characteristics of seronegative and musk myasthenia gravis - Huda, S (2017)
Myasthenia gravis (MG) is an autoimmune disorder of the neuromuscular junction (NMJ). Most patients have antibodies (Abs) against the acetylcholine receptor (AChR) or muscle specific kinase (MuSK) detected by radioimmunoassays (RIAs). Cell-based assays can more sensitively detect these and other Abs (e.g. to low density lipoprotein receptor-related protein 4 (LRP4)) but no large cohorts of MG patients have been systematically studied. RIA positive MuSK-Abs are mainly IgG4 subclass and block the interaction between LRP4 and MuSK, resulting in reduced MuSK phosphorylation and agrin-induced AChR clustering at the NMJ. MuSK phosphorylation could provide a potential therapeutic target. An international cohort of 231 MG patients negative for AChR and MuSK Abs by RIA, were tested with CBAs for all three known antigens. Negative sera were screened for novel antigenic targets by immunoprecipitation and mass spectrometry (IP/MS). MuSK phosphorylation was assessed in cultured mouse C2C12 myotubes treated with MuSK-MG IgG subclass fractions. The formation, dispersal, and re-formation of AChR clusters by MuSK-Abs in the presence or absence of a tyrosine phosphatase SHP2 inhibitor (NSC-87877) were measured quantitatively. First, the detection of MuSK-IgG Abs by CBA was optimised, and the potential relevance of the antibodies shown by their ability to reduce agrin-induced AChR clusters in the myotubes. Overall, AChR-Abs (10%), MuSK-Abs (7%) and LRP4-Abs (<1%) antibodies were newly identified. Five negative sera bound to human muscle cell lines, but no plausible novel antigens were identified by IP/MS. MuSK-MG IgG4 fractions inhibited MuSK phosphorylation, which was restored by SHP2 inhibition. SHP2 inhibition also increased AChR cluster formation, blocked dispersal and increased re-formation of AChR clusters by MuSK-Abs. As discussed, finding new antibody targets in MG was confounded by testing patients who were no longer severely affected following immunotherapies. MuSK-MG, by contrast, is frequently severe and modifying phosphorylation of MuSK and its downstream signalling pathways may provide a novel treatment approach for this and other forms of MG.